2020
DOI: 10.1111/acem.13959
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Focused Assessment With Sonography for Trauma Enhanced Physical Examination in Children With Blunt Torso Trauma

Abstract: Objectives Computed tomography (CT), the reference standard for diagnosis of intraabdominal injury (IAI), carries risk including ionizing radiation. CT‐sparing clinical decision rules for children have relied heavily on physical examination, but they did not include focused assessment with sonography for trauma (FAST), which has emerged into widespread use during the past decade. We sought to determine the independent associations of physical examination, laboratory studies, and FAST with identification of IAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…A similar study has shown that the use of FAST and physical examination together could predict intraabdominal trauma. However, the joint use of FAST and physical examination had higher sensitivity and negative predictive value compared to their separate uses [19]. Different from their ndings, another study showed that FAST did not contribute to clinical intervention in pediatric patients with blunt torso trauma who were hemodynamically stable and treated in the emergency department, thus not recommending its use in emergency departments for pediatric patients [20].…”
Section: Discussionmentioning
confidence: 85%
“…A similar study has shown that the use of FAST and physical examination together could predict intraabdominal trauma. However, the joint use of FAST and physical examination had higher sensitivity and negative predictive value compared to their separate uses [19]. Different from their ndings, another study showed that FAST did not contribute to clinical intervention in pediatric patients with blunt torso trauma who were hemodynamically stable and treated in the emergency department, thus not recommending its use in emergency departments for pediatric patients [20].…”
Section: Discussionmentioning
confidence: 85%
“…(3-5) Expertise in FAST improves the overall accuracy of the study, and therefore, the utility in potentially reducing unnecessary CT use. (6) However, barriers in education, training, skill maintenance, and quality assurance have perpetuated a lack of global FAST expertise. (3, 7, 8) This lack of expertise is often cited as the primary reason for FAST not being accurately implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…FAST decreases computed tomography usage and improves clinical outcomes in adults with blunt injury, 1 but has shown inconsistent diagnostic utility in children. 2,3 This inconsistency of FAST in children arises from varying image acquisition and interpretation of all the possible views. [4][5][6] Specifically, noninterpretable FAST views are a major source of technical error.…”
mentioning
confidence: 99%
“…[4][5][6] Specifically, noninterpretable FAST views are a major source of technical error. 7 Technical expertise improves FAST diagnostic consistency and accuracy, 3 however, there remain barriers in education, training, and skill maintenance that have perpetuated a lack of global pediatric FAST expertise. 4,8,9 This lack of expertise is a primary reason for FAST not being universally implemented in pediatric clinical practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation